High Ecophysiological Plasticity of Desmarestia aculeata (Phaeophyceae) Present in an Arctic Fjord under Varying Salinity and Irradiance Conditions - Marambio Gallardo, Johanna Valeska; Diehl, Nora; Bischof, Kai (My University, 2022)
Simple Summary The Arctic region has been affected by rising temperatures, directly affecting the organisms living there. One of the organisms that inhabit this area is the seaweed Desmarestia aculeata (Phaeophyceae), widely distributed in the North Atlantic. It is exposed to the high Arctic light regime and fluctuating salinity conditions from glacial and terrestrial run-off. Despite its abundance, little is known about D. aculeata and how environmental drivers will affect it in a future altered by climate change. During the summer of 2019, D. aculeata was collected in Kongsfjorden, Svalbard (78.9 degrees N, 11.9 degrees E) to investigate its physiological and biochemical responses to salinities of 34, 28, and 18, and daily cycles of irradiance (50-500 mu mol photons m(-2)s(-1)) at 0 degrees C over 21 days. Photosynthetic parameters and high pigment concentrations show how this species has an effective acclimation to irradiance changes, being unaffected by low salinity. The high concentration of antioxidant phlorotannins at low salinity show how D. aculeata can regulate its daily cycle despite the hyposaline conditions. Salinity and light are interacting factors in the acclimation process. Our work shows the high plasticity of D. aculeata, such that the species will probably be able to tolerate future changes in the Arctic. The seaweed Desmarestia aculeata (Phaeophyceae) is distributed in the temperate zone of the North Atlantic up to the Arctic, where it is exposed to a high Arctic light regime and fluctuating salinity conditions resulting from glacial and terrestrial run-off. Information on how this species is able to thrive under current and future Arctic conditions is scarce. During the Arctic summer of 2019, D. aculeata was collected in Kongsfjorden, Svalbard (78.9 degrees N, 11.9 degrees E) to investigate its physiological and biochemical responses to variations in salinity (salinities: 34, 28 and 18) and daily cycles of irradiance (50-500 mu mol photons m(-2)s(-1)) at 0 degrees C over 21 days. The species revealed effective short-term acclimation to both abiotic drivers. Maximal quantum yield of PSII (F-v/F-m) fluctuated with the light cycle at a salinity of 34, while the maximum relative electron transport rate (rETRmax) significantly differed between salinities of 28 and 18. Chlorophyll a and beta-Carotene remained at high concentrations in all treatments showing pronounced acclimation during the experiment. High mannitol concentrations were measured throughout the experiment, while phlorotannins were high at low salinity. Hyposalinity and light are interacting drivers of the physiological and biochemical acclimation process for D. aculeata. Our experiment highlights the high ecophysiological plasticity of D. aculeata, suggesting that the species will likely be capable of withstanding future habitat changes in the Arctic.
Keywords: arctic; mannitol; acclimation; f-v; f-m; pigments